2021
DOI: 10.3390/app11073099
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Kazakhstani and European Design Specifications: Raft Foundation, Pile Foundation, and Piled Raft Foundation

Abstract: The introduction of Eurocode in Kazakhstan allows for the application of modern technological innovations and the elimination of technical barriers for the realization of international projects. It is significant to study the international standards and design requirements provided in Eurocode. This study presents a comparative analysis of Kazakhstani and European approaches for the geotechnical design of foundations and provides the design methods in the considered codes of practice. Three different types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…𝑅 𝑝 = 𝐴 𝑝 𝑞 ′ 𝑁 𝑞 * ≤ 𝐴 𝑝 𝑞 𝐿 (9) where: q'effective vertical stress at the pile tip, 𝑁 𝑞 *bearing capacity factor which is a function of friction angle (Das, 2006).…”
Section: Axial Capacity Of Pilesmentioning
confidence: 99%
See 1 more Smart Citation
“…𝑅 𝑝 = 𝐴 𝑝 𝑞 ′ 𝑁 𝑞 * ≤ 𝐴 𝑝 𝑞 𝐿 (9) where: q'effective vertical stress at the pile tip, 𝑁 𝑞 *bearing capacity factor which is a function of friction angle (Das, 2006).…”
Section: Axial Capacity Of Pilesmentioning
confidence: 99%
“…Study by Brown et al [8] indicated that the ranges of diameter and depth of bored piles are 1 m to 2.5 m and 60-90 m, respectively. Bored piles can be constructed using different methods, such as drilling using shafts, drilling under dry condition, installation of caissons and drilled piers [9][10]. Axial resistance of bored piles is summation of the based and skin resistances of the piles.…”
Section: Introductionmentioning
confidence: 99%
“…For 𝑒 ≤ 𝑒 : 𝑁 , = 0.5𝐵𝐿(𝑝 + 𝑝 ), (9) For 𝑒 > 𝑒 : 𝑁 , == ( / ) , (10) For 𝑒 > 𝐵/6 the vertical component of the ultimate resistance of the foundation under seismic load can be obtained as: 𝑁 , = 0.5𝑏 𝐿𝑝 , (11) where 𝑏 = 1.5(𝐵 − 2𝑒 ).…”
Section: Kazakhstani Approach For the Design Of Foundations Of Buildi...mentioning
confidence: 99%
“…Moreover, the application of the European standard for seismic design enables harmonization between sustainability and safety of the design process. The reform in the construction sector involved the gradual transition to the Kazakhstani national standards SP RK EN and National Annexes (NAs) issued in 2016 [9]. The introduced code of practice was recommended for application in parallel with the current normative documents.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the construction industry in the country is associated with the realization of extensive projects [25]. The authors studied the design of different types of foundations (i.e., shallow, pile, and piled raft foundations), adhering to the local and international design codes [36,42]. The previous studies revealed that special attention is required to be paid to the design of foundations.…”
Section: Introductionmentioning
confidence: 99%